2020
DOI: 10.1002/alz.12178
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Chart of Aging: Machine‐learning analytics reveals links between brain aging, white matter disease, amyloid burden, and cognition in the iSTAGING consortium of 10,216 harmonized MR scans

Abstract: Introduction: Relationships between brain atrophy patterns of typical aging and Alzheimer's disease (AD), white matter disease, cognition, and AD neuropathology were investigated via machine learning in a large harmonized magnetic resonance imaging database (11 studies; 10,216 subjects). Methods: Three brain signatures were calculated: Brain-age, AD-like neurodegeneration, and white matter hyperintensities (WMHs). Brain Charts measured and displayed the relationships of these signatures to cognition and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 43 publications
4
114
0
Order By: Relevance
“…Nevertheless, numerous neuropathological and neuroimaging studies indicate that white matter (WM) abnormalities are also commonly present among AD patients [3][4][5][6][7][8]. While these findings have been traditionally interpreted as comorbidities, accumulating evidence from our group [9] and others [10][11][12][13][14] points towards a link between WM pathology and AD-specific neuropathologic changes, suggesting that WM degeneration is a characteristic feature of the AD pathological cascade. Among these pathological changes, one of the most prominent is the generalized degradation of axonal myelin sheets in cerebral WM [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, numerous neuropathological and neuroimaging studies indicate that white matter (WM) abnormalities are also commonly present among AD patients [3][4][5][6][7][8]. While these findings have been traditionally interpreted as comorbidities, accumulating evidence from our group [9] and others [10][11][12][13][14] points towards a link between WM pathology and AD-specific neuropathologic changes, suggesting that WM degeneration is a characteristic feature of the AD pathological cascade. Among these pathological changes, one of the most prominent is the generalized degradation of axonal myelin sheets in cerebral WM [15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“… 1 , 2 , 4 White matter hyperintensities are associated with an increased risk of dementia, cognitive decline, stroke, death, abnormal gait, disturbed balance, and depression. 1 , 2 , 4 , 6 , 7 Habes et al 5 , 8 reported higher WMH burden to be associated with advanced brain aging and increased brain atrophy patterns related to Alzheimer disease (AD) in the Study of Health in Pomerania (SHIP). A recent longitudinal study 9 reported associations between greater WMH burden and accelerated cognitive, neuropsychiatric, and functional decline independent of traditional AD risk factors and MRI biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, numerous neuropathological and neuroimaging studies indicate that white matter (WM) abnormalities are also commonly present among AD patients [3][4][5][6][7][8]. While these ndings have been traditionally interpreted as comorbidities, accumulating evidence from our group [9] and others [10][11][12][13][14] points towards a link between WM pathology and AD-speci c neuropathologic changes, suggesting that WM degeneration is a characteristic feature of the AD pathological cascade. Among these pathological changes, one of the most prominent is the generalized degradation of axonal myelin sheets in cerebral WM [15][16][17].…”
Section: Introductionmentioning
confidence: 99%